Organizational culture, authentic leadership and quality improvement in Canadian healthcare facilities - Andrea Bernardes; Carmen Silvia Gabriel; Greta G. Cummings; Ariane Cristina Barboza Zanetti; Alexandre Bevilacqua Leoneti; Graziela Caldana; Vanessa Gomes Maziero (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To investigate relationships among flexible and hierarchical organizational cultures, quality improvement domains, and authentic leadership competencies in Canadian healthcare facilities. Method: Observational cross-sectional study conducted in Alberta, Canada. Nurse managers (n=226) completed a survey including validated measures of organizational culture, quality improvement and authentic leadership. Data were analyzed using descriptive statistics, Spearman's correlation coefficient and Chi-squared test (p<0.05). Results: Quality improvement through accreditation is related to organizational culture and authentic leadership. We saw a propensity for participants who reported working in a more flexible culture also reported greater quality improvement implementation and authentic leadership practices. Conclusion: This study assessed and reported the relationships between flexible organizational cultures, quality improvement through the accreditation process, and authentic leadership practices of healthcare managers. Flexible organizational cultures influence the adoption of authentic leadership, participatory management model and also improves quality.